Measuring Creative Thinking Skills Using the Feasibility of Mathematics Problems with an Open-Ended Approach in Two-Dimensional Plane Geometry Topic - Setyaedhi, Hari Sugiharto; Arianto, Fajar; Mubarok, Husni (Jurnal Pendidikan MIPA, 2025)
The study aims to develop and validate open-ended mathematics questions, where measuring students' abilities at the field test stage is part of the final validation process to show that the instrument is functional. The development model with Tessmer's formative evaluation approach includes self-evaluation, expert review, one-to-one, small group, and field tests. The participants included one lecturer, two mathematics teachers, and students from grade IX. Individual trials involved three students, small group trials 12 students, and field trials 40 students. The data obtained came from quantitative and qualitative data. The instruments used included observation sheets, interviews, questionnaires, and tests. Analysis for quantitative data was carried out using the SPSS application. The findings of the study indicate that (1) this study produces a mathematics question product with an open-ended approach of 5 descriptive questions. Content validity (90.33%), construct validity (94.25%), and language validity (92.25%). High validity is caused by the formulation of questions that explicitly ask students to provide various ways, which directly target indicators of fluency and flexibility in creative thinking. In addition, the validity of each question item in the small group, namely r count > r table (0.576), with a reliability value of 0.931. (2) Open-ended math questions that are valid and reliable, so that they are used to measure students' creative skills in problem solving. Based on the results of the field test (20% of students are very creative, 30% creative, 10% quite creative, 5% not creative, and 5% very not creative), this proves that the instrument developed is able to differentiate the level of student ability. This study concludes that the development of math questions with an open-ended approach is feasible to be applied to measure creative thinking skills in solving math problems related to the two-dimensional plane geometry topic.      Keywords: creative skills, feasibility of mathematical problems, open-ended approach, two-dimensional plane geometry topic.